Crime, punishment, and responsibility the jurisprudence of Antony Duff - Cruft, Rowan; Kramer, Matthew H., 1959-; Reiff, Mark R., 1957- (Oxford : Oxford University Press, 2011)
For many years, Antony Duff has been one of the world's foremost philosophers of criminal law. This volume collects essays by leading criminal law theorists to explore the principal themes in his work. In a response to the essays, Duff clarifies and develops his position on central problems in criminal law theory.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Duff, Antony; Criminal law